EFFECT OF BREADFRUIT LEAF EXTRACT ON THE VIABILITY OF STREPTOCOCCUS MUTANS BIOFILM IN VITRO - ZULFIKAR, SEPTI WARDA; UTAMI, SRI; FARIDA, RATNA (International Journal of Applied Pharmaceutics, 2019)
Objective: Breadfruit leaf has potent antibacterial properties that could be used to reduce biofilms in the oral cavity. The purpose of this study was to analyze the antibacterial effect of the breadfruit leaf extract on the growth of Streptococcus mutans in vitro. Methods: S. mutans ATCC 25175 was cultured in a 96-well plate and incubated at 37°C for 20 h (accumulation phase) and 24 h (maturation phase). The breadfruit leaf extract was added at the following concentrations: 5%, 10%, 15%, 20%, 40%, 80%, and 100%. The viability of S. mutans was tested with the MTT assay at a wavelength of 490 nm. The results were analyzed by one-way analysis of variance. Results: In the accumulation phase, a significant decrease was found in S. mutans viability at different concentrations of the breadfruit leaf extract, but in the maturation phase, a significant decrease was found in the S. mutans viability at the 5% concentration. The other groups decreased significantly compared with the control group (*p<0.05). The viability of S. mutans after adding the breadfruit leaf extract at all concentrations was lower in the accumulation phase than that in the maturation phase. Conclusion: In the accumulation phase, breadfruit leaf extract at concentrations of 5%, 10%, 20%, 40%, 80%, and 100% can reduce S. mutans biofilm viability.